Penyalahgunaan Wewenang dalam Tindak Pidana Kekerasan Seksual yang Dilakukan oleh ASN (Studi Putusan Nomor: 265/Pid.Sus/2024/Pn Nnk) - Putra Hartama Damanik (Riviera Publishing, 2025)
This study analyzes abuse of authority by State Civil Apparatus (ASN) in sexual violence crimes, focusing on the case of Nunukan District Court Decision Number 265/Pid.Sus/2024/PN Nnk. The purpose of this study is to identify the forms of abuse of authority by ASN, examine the perpetrator's criminal liability, and evaluate the judge's considerations in constructing abuse of office as an aggravating element of criminal punishment according to Law Number 12 of 2022 concerning Sexual Violence Crimes (TPKS Law). The method used is normative juridical with a statutory and case approach. The data used includes related laws, government regulations, as well as previous literature and research. The results of the study indicate that the ASN in this case has abused his position for personal gain, fulfilling the elements of Article 6 letter c of the TPKS Law and Article 52 of the Criminal Code. However, the judge has not fully considered abuse of office as an aggravating factor, resulting in a lighter sentence than the prosecutor's demands. This research emphasizes the need to strengthen laws governing sanctions for civil servants who commit acts of sexual violence, both criminal and administrative, including dishonorable discharge, to ensure accountability and protection of victims.